Two distinct forms of human BLT2: long-form and short-form BLT2 - Wei, Jun-Dong; Kim, Jae-Hong (Frontiers in Cell and Developmental Biology, 2023)
BLT2 is a low-affinity leukotriene B 4 receptor that plays an essential role in the pathogenesis of various inflammatory diseases, including asthma and cancer. BLT2 is minimally expressed in a normal internal environment but is overexpressed in a stress-induced inflammatory environment. Recent research indicated that human BLT2 has two distinct forms. Although their functions are likely to be different, very few studies investigated these differences.Therefore, this paper will discuss about the two distinct forms of human BLT2; the short-form of BLT2 and the long-form of BLT2.